Impact of accentuated cut edges (ACE) technique on volatile and sensory profiles of Shiraz wines. (15th March 2022) - Wang, Xingchen; Capone, Dimitra L.; Kang, Wenyu; Roland, Aurélie; Jeffery, David W.
Highlights: Accentuated cut edges (ACE) technique was applied to Shiraz winemaking. Thiols, thiol precursors and other volatiles were compared to conventional crushing. ACE had no effect on thiol precursors in must but concentrations were lower in wine. Shorter skin contact time significantly increased thiol concentration in wine. Treatment interaction impacted acetates, higher alcohols, fatty acids, isoprenoids. Abstract: Varietal thiols are important wine aroma compounds that are generally less abundant in red wines. Accentuated cut edges (ACE), known for accelerating phenolic extraction, was applied to Shiraz winemaking and compared with conventional crushing (NOACE) to examine the effects on varietal thiol precursor extraction and thiol formation. Water addition to grape must and skin contact time (SCT) during fermentation were also assessed. Although there was no difference for precursors in the must, ACE significantly decreased 3- S -glutathionylhexan-1-ol concentration during fermentation. 3-Sulfanylhexan-1-ol and ethyl esters were significantly influenced by crushing method and/or SCT, with NOACE or shorter SCT yielding higher concentrations. Acetates, higher alcohols, fatty acids, and isoprenoids differed according to the interaction of crushing method and SCT, with ACE and shorter SCT significantly enhancing all groups except acetates. Volatiles in Sauvignon blanc and Pinot noir wines produced at commercial scale with ACE were briefly evaluated, suggesting an impact of grape variety.